Determining the optimal time interval for cholecystectomy in moderate to severe gallstone pancreatitis: A systematic review of published evidence. (December 2020) - Hughes, Daniel Llwyd; Morris-Stiff, Gareth
Abstract: Background: /Objectives: A paradigm shift has been observed in the management of mild gallstone pancreatitis; current guidelines advocate definitive cholecystectomy on the index admission. Despite the abundance of published guidelines, uncertainty remains with regard to the timing of cholecystectomy in moderate and severe acute pancreatitis (MAP/SAP), and no definitive consensus has been declared. This systematic review aimed to evaluate the published guidelines and subsequent evidence quoted in order to determine the optimal timing for cholecystectomy in this high-risk patient cohort. Method: A systematic review of published literature was performed using PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) and AMSTAR (Assessing the methodological quality of systematic reviews) guidelines, and included a search of three online electronic databases. Results: Eleven guidelines were included. Only 4 (36%) of guidelines specified an actual time frame for surgical intervention. Delaying surgery for a minimum of 6 weeks was advocated by all 4 guidelines. All recommendations were based upon weak or very low-quality evidence. Higher mortality rates were observed when patients underwent early cholecystectomy for SAP (1.3–44%) when compared to patients who underwent delayed surgery (0–11%). Conclusion: Marked variation was observed amongst the published guidelines on the definitive management of MAP and SAP and disparity remains on the timing of cholecystectomy. A minority of the guidelines proposed a specific time period for when cholecystectomy should be performed, and whilst based on low quality evidence, delaying surgery (for 6 weeks) is associated with a reduction in morbidity and mortality rates and should be advocated in MAP/SAP until level 1 evidence becomes available. Highlights: The timing of cholecystectomy in moderate and severe acute pancreatitis (MAP/SAP) remains uncertain and no definitive consensus has been declared. This systematic review illustrates the variability in the published guidelines on the timing of definitive surgery (cholecystectomy) in MAP/SAP. The overall quality of the evidence used to create the guidelines were of low quality from historical data that may not be representative of current clinical practice. Data suggests that an interval cholecystectomy in this cohort is indicated as it leads to a significant reduction in morbidity and mortality rates.